2010
DOI: 10.1186/2042-6410-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex dependent regulation of osteoblast response to implant surface properties by systemic hormones

Abstract: BackgroundOsseointegration depends on the implant surface, bone quality and the local and systemic host environment, which can differ in male and female patients. This study was undertaken in order to determine if male and female cells respond differently to titanium surfaces that have micron-scale roughness and if interactions of calciotropic hormones [1α,25(OH)2D3 and 17β-oestradiol (E2)] and microstructured surfaces on osteoblasts are sex dependent.MethodsOsteoblasts from 6-week old Sprague-Dawley rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…They have been well studied in cell response to titanium (32) and results correlate well with results obtained from in vitro studies using normal human osteoblasts, fetal and adult rat calvarial osteoblasts, and neonatal mouse calvarial osteoblasts (3337) as well as with in vivo osseointegration of dental and orthopaedic implants (11, 12, 25). Cells were cultured at an initial density of 10,000 cells/cm 2 on tissue culture polystyrene (TCPS, the surface of the cell culture plate wells), PEEK, sTiAlV, and rTiAlV.…”
Section: Methodsmentioning
confidence: 56%
See 1 more Smart Citation
“…They have been well studied in cell response to titanium (32) and results correlate well with results obtained from in vitro studies using normal human osteoblasts, fetal and adult rat calvarial osteoblasts, and neonatal mouse calvarial osteoblasts (3337) as well as with in vivo osseointegration of dental and orthopaedic implants (11, 12, 25). Cells were cultured at an initial density of 10,000 cells/cm 2 on tissue culture polystyrene (TCPS, the surface of the cell culture plate wells), PEEK, sTiAlV, and rTiAlV.…”
Section: Methodsmentioning
confidence: 56%
“…Conditioned media were collected and assayed for secreted proteins and factors as described previously (33). OPG, VEGF-A, FGF-2, and Ang-1 were assayed using commercially available enzyme-linked immunosorbent assays (R&D Systems, Minneapolis, MN) following manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The deficiency of biglycan on chromosome X strongly affects male bones (34,35). Furthermore, Olivares-Navarrete et al (36) reported a sex difference in osteogenic response to vitamin D treatment in primary osteoblasts. These findings suggest that a protein linked to sex chromosome might be responsible for the sex difference observed in response to PAI-1 in primary osteoblasts in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Primary human osteoblasts (hOBs) were isolated from vertebral bone of a 17-year-old male that was collected under Institutional Review Board approval from Children’s Healthcare of Atlanta and Georgia Institute of Technology, as described previously (9). hOBs were allowed to migrate from the bone fragments to the culture plate and, at confluence, the cells were further passaged for experiments and were cultured in Dulbecco’s modified Eagle medium (DMEM; Corning cellgro ® , Manassas, VA) containing 10% fetal bovine serum (Life Technologies, Carlsbad, CA) and 1% penicillin-streptomycin (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%